Overcoming choice inertia through social interaction: An agent-based study of mobile subscription decision - Barsha Saha; Miguel Martínez-García; Sharad Nath Bhattacharya; Rohit Joshi (Games, 2022)
Subscription decision in the telecom market is quite complex and cumbersome, invoking decision inertia in consumers and resulting in suboptimal choices. We implemented choice inertia and consumer interaction as an agent-based model to better understand the process. The model illustrates that with adequate peer interactions with active consumers, inactive consumers could overcome their inertia significantly and switch to a better alternative. Furthermore, the newly converted active consumers influenced their inert neighbors as a ripple effect. Active consumers contribute to firm profits and healthy market competition. Moreover, in environments with low neighborhood effects and a stronger inertia threshold, firms are able to maintain profits by retaining inert consumers. We show that apart from the attractiveness of market offerings, firms can benefit from understanding consumer inertia and devising means to reduce it.
Keywords: 330; agent-based modelling; competition; complexity; consumer behavior (inertia); game theory; homophily; telecommunications